SOCIAL JUSTICE AND ACCESS TO HEALTH IN CIREBON REGENCY - Mohamad Sigit Gunawan Gunawan; Siska Karina (Faculty of Law, Universitas Pekalongan, 2025)
The 5th Pancasila Precept, which reads social justice for the community, includes justice in all aspects, including social justice in the health sector. The government has issued various regulations to implement the fifth precept of Pancasila, but in some areas, problems have arisen in the health sector. The national health program adopted by WHO is the UHC Program. One of the benefits provided by the UHC program is the active participation of 1x24 hours, but with the UHC program, several requirements must be met by local governments that cause new problems. This research method uses a qualitative research method that emphasizes in-depth understanding. The research was conducted in Cirebon Regency using data from the Health Office and Social Service and interviews with private hospitals. Cirebon Regency is an autonomous region with its inherent concurrent authority to make policies in the field of health services so that health service problems can be solved and the people of Cirebon Regency can feel social justice in the health sector.